Current Diabetes Reports - Goldberg, Ronald B.; Florez, Jose C.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
The goal of this journal is to publish cutting-edge reviews on subjects pertinent to all aspects of diabetes epidemiology, pathophysiology, and management. We aim to provide incisive, insightful, and balanced contributions from leading experts in each relevant domain that will be of immediate interest to a wide readership of clinicians, basic scientists, and translational investigators. We accomplish this aim by appointing major authorities to serve as Section Editors in key subject areas across the discipline. Section Editors select topics to be reviewed by leading experts who emphasize recent developments and highlight important papers published over the past year on their topics, in a crisp and readable format. We also provide commentaries from well-known figures in the field, and an Editorial Board of internationally diverse members suggests topics of special interest to their country/region and ensures that topics are current and include emerging research.
Keywords: Diabetes; Diabetes